2023
DOI: 10.31450/ukrjnd.2(78).2023.07
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing serum indoxyl sulfate and COVID-19 outcomes in patients undergoing hemodialysis: A retrospective cohort study

Abstract: Patients undergoing hemodialysis (HD) are at increased risk of severe complications from COVID-19 due to compromised immune function and comorbidities. This retrospective study aimed to investigate the association between pre-existing serum indoxyl sulfate (IS) concentrations and COVID-19 outcomes in HD patients. Methods. Data on pre-existing IS and proinflammatory cytokines, such as interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor-alpha (TNF-α) were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…36 Moreover, our previous report demonstrated that increased preexisting serum indoxyl sulfate was associated with poor COVID-19 outcomes in HD patients, including the severity of pulmonary damage observed on CT scans. 4 Although our study did not directly measure cytokine levels due to its retrospective nature, a notable increase in CRP levels was observed in patients with spKt/V <1.4 compared to those with spKt/V ≥1.4. This finding also implies a potential association between dialysis adequacy and inflammatory markers.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…36 Moreover, our previous report demonstrated that increased preexisting serum indoxyl sulfate was associated with poor COVID-19 outcomes in HD patients, including the severity of pulmonary damage observed on CT scans. 4 Although our study did not directly measure cytokine levels due to its retrospective nature, a notable increase in CRP levels was observed in patients with spKt/V <1.4 compared to those with spKt/V ≥1.4. This finding also implies a potential association between dialysis adequacy and inflammatory markers.…”
Section: Discussionmentioning
confidence: 81%
“…2,3 Patients undergoing HD are at higher risk of contracting COVID-19 and related complications due to multifactorial risks, including underlying comorbidities, immunosuppression, and frequent dialysis facility visits, which contribute to their increased vulnerability. [2][3][4] Vaccination against SARS-CoV-2 has been found to be highly effective in preventing severe illness, hospitalization, and death in the HD population. 5,6 However, recent studies have suggested that even fully vaccinated individuals, including patients undergoing HD, may still develop long-term COVID, a condition characterized by persistent symptoms that extend beyond the acute phase of COVID-19.…”
Section: Introductionmentioning
confidence: 99%